Optotracing for live selective fluorescence-based detection of Candida albicans biofilms - Kärkkäinen, Elina; Jakobsson, Saga G.; Edlund, Ulrica; Richter-Dahlfors, Agneta; Choong, Ferdinand X. (Frontiers in Cellular and Infection Microbiology, 2022)
Candida albicans is the most common fungal pathogen in humans, implicated in hospital-acquired infections, secondary infections in human immunodeficiency virus (HIV) patients, and is a significant contributor to the global antimicrobial resistance (AMR) burden. Early detection of this pathogen is needed to guide preventative strategies and the selection and development of therapeutic treatments. Fungal biofilms are a unique heterogeneous mix of cell types, extracellular carbohydrates and amyloid aggregates. Perhaps due to the dominance of carbohydrates in fungi, to date, few specific methods are available for the detection of fungal biofilms. Here we present a new optotracing-based method for the detection and analysis of yeast and biofilms based on C. albicans SC5314 as a model. Using commercial extracts of cell wall carbohydrates, we showed the capability of the optotracer EbbaBiolight 680 for detecting chitin and β-glucans. The sensitivity of this tracer to these carbohydrates in their native environment within fungal cells enabled the visualization of both yeast and hyphal forms of the microbe. Analysis of optotracer fluorescence by confocal laser scanning microscopy revealed extensive staining of fungi cell walls as well as the presence of intracellular amyloid aggregates within a subpopulation of cells within the biofilm. Further analysis of the photophysical properties of bound tracers by spectroscopy and spectral imaging revealed polymorphisms between amyloid aggregates within yeast and hyphal cells and enabled their differentiation. With exceptional spatial and temporal resolution, this assay adds a new technique that facilitates future understanding of fungal biofilms and their formation, and enables direct, unbiased diagnostics of these medically relevant biofilms, as well as the development of antifungal strategies.